Sumbangan Tuan Guru Haji Omar Ahmad dalam Bidang Keilmuwan di Terengganu - Abd. Latif, Faizuri (Jurnal Usuluddin, 2006)
The present Muslim society is perceived to know more about entertainers than ulama who have contributed greatly to the development of the society. Thus, the aim of this article is to introduce an ulama whose contribution has played a major role in the development of Islamic education in the district of Besut in Terengganu. It is hoped that through this article his enormous contributions will always be appreciated and remembered.